Talk COVID to me: Language rights and canadian government responses to the pandemic - Chouinard, Stéphanie; Normand, Martin (Canadian Journal of Political Science, 2020)
Since the COVID-19 outbreak, a gradual loosening of linguistic obligations in public institutions and governments has been observed in various jurisdictions in Canada. This article argues that in addition to legal requirements to provide minority language services, it is not justifiable for governments to suspend or curtail such services in an emergency situation, for reasons pertaining to public safety and public health. After performing a survey and analysis of government actions against their constitutional, legislative, and policy language obligations to highlight best practices and deficiencies, we discuss the policy implications of these actions. In conclusion, the article considers how governments could better uphold their language obligations in times of emergency.

Impact of language barriers on quality of care and patient safety for official language minority Francophones in Canada - de Moissac, Danielle; Bowen, Sarah (Journal of Patient Experience, 2019)
Introduction: The risks to patient safety and quality of care faced by members of linguistic minority groups have been well-documented. However, little research has focused on the experience of official language minorities in Canada. Methods: This multiple method study (online and paper-based surveys combined with semi-structured individual interviews with patients and interpreters-health navigators) explored the experience of minority Francophones living in 4 Canadian provinces. Results: Patients and interpreters-navigators described experiences where language barriers contributed to poorer patient assessment, misdiagnosis and/or delayed treatment, incomplete understanding of patient condition and prescribed treatment, and impaired confidence in services received. Reliance on Google Translate and ad hoc, untrained interpreters are commonly reported, in spite of evidence highlighting the risks associated with such practice. Conclusion: Increased awareness that the risks of language barriers apply to official language minorities is essential.

Insight into Post-Pandemic Needs in Healthcare and Well-Being Among Francophone Families in the Canadian Prairies - Keough, Catelyn; Turgeon, Marianne; Proulx-Cullen, Elyse; Leis, Anne; De Moissac, Danielle; Marchak, Kristan; Gnidehou, Sedami (International Journal of Environmental Research and Public Health, 2026)
Francophone populations outside Quebec were disproportionately affected by the COVID-19 crisis. Despite French being one of Canada’s official languages, access to information and services in French remains limited. This study examined Francophone families’ (FF) post-pandemic health and well-being needs (PPHW) in the Canadian Prairie provinces. An online survey assessed PPHW needs among 319 FF in Alberta (AB), Saskatchewan (SK), and Manitoba (MB). Respondents ranked PPHW needs from a predefined list; logistic regression analyzed socio-demographic influences. Divided into AB/SK and MB cohorts, sociodemographic profiles were statistically distinct for many variables, but with similarities found in gender of respondents (women: 73% in AB/SK, 79% in MB), marital status (married: 81% in AB/SK, 88% in MB), area of residence (urban: 86% in AB/SK, 81% in MB), and number of children (2 children: 49% in AB/SK, 41% in MB). Three high-priority needs were shared across provinces: (1) access to recreational, athletic, and artistic activities in French for children (variations by child gender); (2) access to French healthcare professionals (variations by education level and language difference); and (3) social activities in French for families. AB/SK respondents prioritized mental health services in French for adults and youth. MB families prioritized belonging to a Francophone community (variations by gender of children) and education services in French (variations by age of children). Understanding these common and province-specific priorities can inform policy and service planning.

Perception du contexte linguistique et culturel minoritaire sur le vécu de la grossesse - Lacaze-Masmonteil, Thierry; Leis, Anne; Lauriol, Emmanuelle; Normandeau, Joane; Moreau, Denise; Bouchard, Louise; Vaillancourt, Cathy (Revue canadienne de santé publique / Canadian Journal of Public Health, 2013)
Objectif Dans une perspective de santé publique, le suivi de grossesse et la période périnatale exigent une communication de qualité et des services de santé qui tiennent compte du contexte dans lequel ces femmes évoluent. Or, des défis d’accès aux services de santé en français en situation minoritaire au Canada ont été documentés. Cette étude pilote a pour objectif de mieux cerner les perceptions et le vécu de femmes enceintes francophones vivant au Canada dans un contexte linguistique minoritaire Méthodes Étant donné la nature exploratoire du questionnement, une étude descriptive alliant des méthodes quantitative et qualitative a été mis en œuvre en Alberta et au Nouveau-Brunswick, dont les populations sont de 2 % et 33 % francophones, respectivement. Deux entrevues semi-structurées et une série de questionnaires ont été administrées auprès de 21 femmes enceintes au début du troisième trimestre de grossesse et à six semaines après la naissance. Une analyse descriptive des questionnaires a permis de dresser le profil et les caractéristiques des participantes, et les entrevues qualitatives, transcrites, codées et analysées de façon inductive par quatre lecteurs indépendants, ont fait ressortir plusieurs thèmes Clés en rapport avec leurs expériences. Résultats La plupart des participantes se sont dites bilingues et la langue ne semble pas avoir été un enjeu majeur dans l’évaluation des services de santé reçus sauf en situation de stress et lors de certaines périodes critiques de la grossesse et de l’accouchement. Par contre, près d’un tiers des participants se disent insatisfaites des services de santé reçus et l’insuffisance de suivi en français est mentionnée comme un des facteurs contribuant à cette insatisfaction. Conclusion Les services de santé sont préférés dans la langue maternelle des femmes mais reçus dans la langue de la majorité la plupart du temps. En situation de stress ou de complication de grossesse, les témoignages des participantes semblent indiquer que la communication en français est un facteur essentiel d’un suivi de grossesse de qualité. Une étude comparative permettrait de mieux distinguer l’impact spécifique de la langue dans l’expérience vécue des femmes enceintes.